Current Progress and Future Directions in the Double Burden of Malnutrition among Women in South and Southeast Asian Countries. Issue 7 (16th May 2019) - Biswas, Tuhin; Townsend, Nick; Magalhaes, R J Soares; Islam, Md Saimul; Hasan, Md Mehedi; Mamun, Abdullah
ABSTRACT: Background: In order to combat the double burden of malnutrition the UN General Assembly has established under its Sustainable Development Goal-2 (SDG2) a set of nutritional targets that member countries need to achieve by 2030, with the goal of eradicating all forms of malnutrition worldwide. Objectives: In order to understand progress towards this goal, we reviewed recent trends and forecast future trends to examine the likelihood of South and Southeast Asian countries achieving the SDG2 target by 2030. We also considered how inequalities based on wealth, education, and urban/rural dwelling influence the current and future prevalence of underweight, overweight, and obesity. Methods: We used population-representative cross-sectional data from the Demographic and Health Survey, conducted between 1996 and 2016, for 8 South and Southeast Asian countries. We used a Bayesian linear regression model to estimate trends and to forecast the prevalence of underweight, overweight, and obesity by 2030. Results: The overall pooled prevalence of underweight, overweight, and obesity in the South and Southeast Asian region was 22.9%, 21.3%, and 8.6%, respectively. Regional average annual rate of reduction and average annual rate of increase for the period 1996 to 2016 were 1.3% and 8.4% for underweight and overweight/obesity respectively. We estimate that if current trends continue as projected, the proportion of underweight and overweight/obesity will be 6.6% (95% CI: 3.9%, 11.1%) and 76.6% (95% CI: 64.3%, 85.7%) in 2030, respectively. Specific projections based on the wealth index suggested that by 2030 the prevalence of underweight would be highest among the poorest sector of society, and overweight and obesity highest among the richest sector. Conclusions: We found that despite progress in reducing underweight, nearly two-thirds of the South and Southeast Asian population will be overweight or obese by 2030. Our findings suggest that countries in this region will not achieve the 2030 SDG2 target.